Development of a tailored intervention targeting sedentary behavior and physical activity in people with stroke and diabetes: A qualitative study using a co-creation framework - Bodilsen, Stefan Sjørslev; Aadahl, Mette; Wienecke, Troels; Thomsen, Trine Hørmann (Frontiers in Rehabilitation Sciences, 2023)
Abstract Purpose Type 2 diabetes and sedentary behavior pose serious health risks in stroke survivors. Using a co-creation framework, this study aimed to develop an intervention in collaboration with stroke survivors with type 2 diabetes, relatives, and cross-sectoral health care professionals to reduce sedentary behavior and increase physical activity. Materials and methods This qualitative explorative study used a co-creation framework consisting of a workshop and focus group interviews with stroke survivors with type 2 diabetes (n=3), relative (n=1), and healthcare professionals (n=10) to develop the intervention. A content analysis was used to analyze data. Results The developed Everyday Life is Rehabilitation (ELiR) intervention consisted of a tailored 12-week home-based behavior change intervention with two consultations of action planning, goal setting, motivational interviewing, and fatigue management including education on sedentary behavior, physical activity, and fatigue. The intervention has a minimalistic setup using a double-page paper “Everyday Life is Rehabilitation” (ELiR) instrument making it implementable and tangible. Conclusions In this study, a theoretical framework was used to develop a tailored 12-week home-based behavior change intervention. Strategies to reduce sedentary behavior and increase physical activity through activities of daily living along with fatigue management in stroke survivors with type 2 diabetes were identified.